Comparison Between Traditional and Modern Approaches in Arabic Language Teaching - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (Gunung Djati Conference Series, 2025)
This study aims to analyze the similarities, differences, strengths, and weaknesses between traditional and modern approaches in teaching Arabic. Employing a qualitative approach through a comparative study method, the research examines both approaches to identify their respective advantages and limitations in Arabic language instruction. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, presentation, and inductive conclusion drawing, resulting in a comprehensive portrayal grounded in empirical findings and theoretical literature. The results indicate that Arabic language teaching has evolved from traditional methods centered on memorization and grammar toward modern approaches emphasizing communication, collaboration, and technology integration. Both approaches share the goal of equipping students with oral and written skills, with the teacher’s role and assessment remaining essential. The traditional approach excels in grammatical depth, while the modern approach excels in interactivity. The shortcomings of each approach necessitate that teachers select strategies aligned with students’ needs and learning objectives. The findings recommend combining the best elements of both approaches to develop an Arabic language teaching model that is balanced, relevant to contemporary needs, and firmly rooted in scholarly traditions and Arab-Islamic cultural values.